A Nurse mailing list serving the Dialysis at Home community - Marie PADERNOZ (RDPLF, 2019)
Aware of the difficulties encountered by the centers in the outpatient management of peritoneal dialysis patients, on March 21, 2016, the French Language Peritoneal Dialysis Registry (RDPLF) launched an «alloDP» nursing list for the benefit of Home Dialysis units active in the Registry. Difficulties in relation to the isolation of the teams, the size of the centers, the number of participants, the lack of knowledge in the technique are undeniably a hindrance to the development of home treatment. This mailing list is exclusively reserved for home dialysis nurses after registration by the RDPLF. They need an email address, if possible, personal. Nephrologists and nurses at the material supply commercial providers may have access to alloDP, upon request, but only as «readers». To break her isolation, or sense of isolation, the nurse simply sends her question, request, or need to the nursing community to the address allodp@rdplf.org. The wealth of sharing does the rest. To illustrate the content of the exchanges, we have chosen to summarize six of them in this article.